Optimizing Fire Safety and Ventilation Strategies for Structural Integrity in Rail Tunnels - Avci-Karatas, Cigdem (Civil Engineering Journal, 2025)
Rail systems are vital to the modern urban infrastructure and offer efficient and eco-friendly transportation solutions. The Gaziray Rail System Line in Gaziantep, Türkiye addresses the region's transportation needs while considering potential hazards such as electrical malfunctions and fuel leaks. This study thoroughly assesses fire occurrences and how they affect the structural integrity of tunnel elements, thereby affecting repair costs and continuity of operations. Fire tests and modeling were employed to precisely assess tunnel fire effects, focusing on potential train fires in Gaziray Rail System Line tunnels. This study highlights the importance of vital airflow for effectively directing smoke. It also identifies the ventilation systems required to ensure optimal airflow while maintaining the structural integrity and evacuation pathways. The study identified 18 jet fans with an outlet velocity of 35.7 m/s and flow rate of 40.4 m³/s, which is essential for safe evacuation. The maximum wall temperatures ranged from 774 to 923°C, highlighting the potential fire severity. Recommendations emphasize fire-resistant materials, optimized ventilation systems, and reinforced emergency evacuation measures that are crucial for enhanced safety. Continuous training and awareness efforts ensure swift and secure evacuation during fire incidents, contributing to robust fire safety protocols for the Gaziray Rail Line. Doi: 10.28991/CEJ-2025-011-02-014 Full Text: PDF